How digital health technologies promote healthy life in the Post-COVID-19 Era: evidences from national survey on Chinese adolescents and youngsters - Li, Xiaojing; Zhang, Min (Frontiers in Public Health, 2023)
The rapid development of intelligent technologies coupled with the stay-at-home trends in the Post-COVID-19 Era has significantly changed youth's health behavior as well as reshaped their lifestyles. Digital health technologies (DHTs) have been more and more used for health management among youngsters. However, little was known about the use of DHTs among youths and its consequences on their health, especially in developing countries like China. Inspired by behavior intervention technology (BIT) model, this study examined the underlying mechanisms of use and social interactions of DHTs on Chinese adolescents' and youngsters' healthy lifestyles and mental health, using a representatively national survey among high school and freshman students in China (N = 2,297). It found that use of DHTs had a significantly positive effect on Chinese youths' healthy lifestyles and mental health, with behavioral regulation as a mediator. However, social interactions of DHTs were negatively associated with their mental health. The findings contribute to a better guidance on health promotion, as well as the enhanced design of DHTs' products.